Preparation of a chemical-regulating block copolymer applied to the thermal connection interface of metal and thermoplastic composite material and regulating method thereof

CN117402305BActive Publication Date: 2026-10-16HARBIN INST OF TECH AT WEIHAI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311318246.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2026-10-16
Estimated Expiration
2043-10-12

AI Technical Summary

Technical Problem

[0007]本发明要解决的问题是现有金属与热塑性复合材料连接界面调控方法对界面连接强度提升效果差、加工时效长、调控作用密度低、成键不明确、共价键诱导困难且不具备定向性的问题,提出一种应用于金属与热塑性复合材料热连接界面的化学调控嵌段共聚物制备及其调控方法

Benefits of technology

[0030] The present invention discloses a method for preparing a chemically regulated block copolymer for use at the thermal interface of a metal and a thermoplastic composite material. This method can induce high-density chemical bonding and secondary interactions between the atoms and functional groups of the metal and the thermoplastic composite material to be bonded. The high-density Si-OM (metal atom) covalent bonds are formed by the de-alcoholization reaction of the KH570 polymer segment in the chemically regulated block copolymer for use at the thermal interface of a metal and a thermoplastic composite material under the action of a catalyst. The polar functional groups of the poly(glycidyl methacrylate) polymer segment interact with the oxygen-containing functional groups (carbonyl groups, ether bonds) inside the thermoplastic composite material in a high-density manner. This invention utilizes a chemically regulated block copolymer prepared for use at the thermal bonding interface of metal and thermoplastic composites. This method employs chemical-scale directional regulation of the interface, leveraging the high polymer interaction density and ease of directional chemical bonding based on atomic composition. This significantly enhances the interfacial bonding strength of metal and thermoplastic composites. By controlling the concentration of the chemically regulated block copolymer and the molecular weight ratio of functional segments within the block copolymer, the interfacial bonding strengthening effect can be adjusted. Furthermore, the regulation size can be adjusted according to the bonding region. The regulation process is simple, convenient, applicable to various thermal bonding processes, and highly adaptable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117402305B_ABST
    Figure CN117402305B_ABST
Patent Text Reader

Abstract

The application relates to a chemical regulation block copolymer applied to a thermal connection interface of metal and thermoplastic composite material and a preparation method thereof, and belongs to the technical field of regulation of the thermal connection interface of metal and thermoplastic composite material. In order to solve the problem of poor connection strength of metal and thermoplastic composite material, a chemical regulation block copolymer applied to a thermal connection interface of metal and thermoplastic composite material and a catalyst are dissolved in an organic solvent to obtain a chemical regulation block copolymer solution, then the solution is sprayed to the surface of metal to be connected, and the metal with a directional regulation coating solidified on the surface is dried at room temperature, then the metal with the directional regulation coating solidified on the surface is assembled in a lap joint mode with thermoplastic composite material to be connected, and high-density covalent bonds and directional induction of secondary interaction of the thermal connection interface of metal and thermoplastic composite material are realized through a thermal connection process. The application realizes application of a functional block copolymer to high-strength connection of metal and thermoplastic composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermal interface control technology for metal-thermoplastic composite materials, specifically relating to a chemically controlled block copolymer preparation and control method for thermal interface control of metal-thermoplastic composite materials. Background Technology

[0002] Lightweighting of equipment, as a crucial means to optimize equipment performance and reduce operation and maintenance costs, has become an inevitable trend in the development of advanced manufacturing equipment. In recent years, carbon fiber reinforced thermoplastic composites, as a new type of high-performance material, possess characteristics such as lightweight, high strength, high rigidity, and impact resistance, and have become a lightweight metal replacement material for industrial applications. Compared to the 10% weight reduction target of dissimilar lightweight metal connection structures, multi-material composite structures connecting metals and thermoplastic composites can achieve a 30-40% weight reduction in local structures of equipment, becoming the main form of current efforts to achieve lightweighting of equipment, and has practical significance for promoting industrial lightweighting and energy conservation and emission reduction.

[0003] Unlike metallurgical bonding at the interface of metallic materials, achieving high-strength bonds at the interface of metals and thermoplastic composites is difficult due to the significant differences in their thermophysical properties. Compared to traditional mechanical and adhesive bonding processes, which suffer from localized weight gain, stress concentration, and environmental pollution, thermal bonding processes, primarily laser bonding, friction stir bonding, and thermocompression bonding, have become the main methods for joining metals and thermoplastic composites due to their advantages such as direct interface bonding, high efficiency, and no environmental pollution, and have become a research hotspot both domestically and internationally. However, the joint strength of a direct bond between two materials relying solely on process optimization is generally low; therefore, the development of interface control processes to strengthen the joint is particularly important.

[0004] The invention patent with application number 202111403530.7 and invention title "A device and method for improving the laser connection strength of metal parts and plastic parts" significantly improves the connection strength between metal and thermoplastic composite materials by preparing a raised microtexture on the metal surface to promote mechanical interlocking. However, the preparation process is relatively complex and has a long process cycle, which is not suitable for the connection of large-sized structural parts, thus limiting industrial production. At the same time, the joint strengthening effect is limited.

[0005] The invention patent with application number 201610590686.3 and invention title "A method for connecting plastic and metal heterostructures" introduces oxides on the metal surface to induce chemical bonding to form a reinforced joint. However, the chemical bonding induced in this way has a low density and is uneven at the connection interface. At the same time, the chemical bonding is not directional, and the bonding is unclear and has a low probability.

[0006] It is evident that existing methods for controlling the interface of metal-thermoplastic composites still have drawbacks in terms of processing aging, control density, chemical bonding orientation, and strengthening effect. New methods for controlling the thermal interface of metal-thermoplastic composites urgently need to be developed. Summary of the Invention

[0007] The problem this invention aims to solve is that existing methods for regulating the interface of metal-thermoplastic composites suffer from poor effects on improving interface strength, long processing time, low density of regulation, unclear bonding, difficulty in inducing covalent bonds, and lack of directionality. This invention proposes a chemically regulated block copolymer preparation and regulation method for the thermal interface of metal-thermoplastic composites.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] A method for preparing a chemically regulated block copolymer for use at the thermal bonding interface of a metal and a thermoplastic composite material includes the following steps:

[0010] S1. Dissolve the initiator, copper bromide, ligand, reducing agent and glycidyl methacrylate in tetrahydrofuran to obtain the reaction system, which is then ready for use.

[0011] S2. The reaction system obtained in step S1 is placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. The mixture is stirred for a certain time under certain temperature conditions to obtain poly(glycidyl methacrylate)-bromine.

[0012] S3. The polyglycidyl methacrylate-bromine obtained in step S2 is extracted by chromatography column to obtain a clear solution and added dropwise to distilled water to obtain a white precipitate. After dehydration treatment, polyglycidyl methacrylate-bromine solid is obtained.

[0013] S4. The poly(glycidyl methacrylate)-bromine obtained in step S3 was added to copper bromide, ligand, reducing agent and KH570 silane coupling agent in tetrahydrofuran, and then placed in a spherical reaction flask for dehydration and deoxygenation using a double-row tube system. After stirring for a certain time under certain temperature conditions, the reaction product was extracted by chromatography column to clarify the solution and then distilled under reduced pressure to obtain a chemically regulated copolymer of the thermal connection interface of metal and thermoplastic composite material.

[0014] The chemical structural formula of the chemically regulated copolymer at the thermal bonding interface between the metal and the thermoplastic composite is as follows:

[0015]

[0016] In the chemical structural formula, n = 10 to 1000, m = n × (10 to 30%).

[0017] Furthermore, in step S1, the molar ratio of the initiator, copper bromide, ligand, reducing agent, and glycidyl methacrylate is 1:0.4:0.4:0.4:n, and the molar volume ratio of glycidyl methacrylate to tetrahydrofuran is 1 mol: 1000 ml.

[0018] Furthermore, the initiator in step S1 is one of ethyl 2-bromopropionate, methyl 2-bromopropionate, or methyl 2-bromoisobutyrate; the ligand is one of pentamethyldiethylenetriamine, 2,2-bipyridine, or hexamethyltriethylenetetramine; and the reducing agent is one of stannous octoate or ascorbic acid.

[0019] Furthermore, the temperature conditions in step S2 are 50-60℃, and the stirring time is 24-30h.

[0020] Furthermore, in step S3, the volume ratio of distilled water to tetrahydrofuran added is 30:1.

[0021] Furthermore, in step S4, the molar ratio of polyglycidyl methacrylate-bromine, copper bromide, ligand, reducing agent and KH570 silane coupling agent is 1:0.4:0.4:0.4:m / n, and the molar volume ratio of KH570 silane coupling agent to tetrahydrofuran is 1 mol:10000 ml; the specific temperature conditions in step S4 are 50-60℃, and the stirring time is 24-30 h.

[0022] A method for regulating chemically controlled block copolymers applied to the thermal bonding interface of metal and thermoplastic composites, based on the aforementioned chemically controlled block copolymers applied to the thermal bonding interface of metal and thermoplastic composites, includes the following steps:

[0023] Step 1: Dissolve the chemically regulated block copolymer and catalyst used in the thermal bonding interface of metal and thermoplastic composite materials in an organic solvent to obtain a chemically regulated block copolymer solution used in the thermal bonding interface of metal and thermoplastic composite materials.

[0024] Step 2: Spray the chemically regulated block copolymer solution obtained in Step 1 onto the surface of the metal to be bonded, and dry it at room temperature for 24 hours to obtain a metal with a directional regulated coating cured on the surface.

[0025] Step 3: Assemble the metal with the directional control coating obtained in Step 2 and the thermoplastic composite material to be joined in an overlapping manner, and obtain a thermal connection joint between the metal and the thermoplastic composite material after the interface directional control through a thermal connection process, so as to realize the directional induction of high-density covalent bonds and secondary interactions at the thermal connection interface between the metal and the thermoplastic composite material.

[0026] Furthermore, the catalyst mentioned in step one is one of dibutyltin dilaurate and stannous octoate, and the organic solvent is one of dichloromethane, tetrahydrofuran, toluene, or chloroform; the concentration of the catalyst in the chemically regulated block copolymer solution applied to the thermal interface of metal and thermoplastic composite is 0.001–0.01 g / mL, and the concentration of the chemically regulated block copolymer applied to the thermal interface of metal and thermoplastic composite is 0.001–0.01 mol / mL.

[0027] Furthermore, in step two, the metal to be connected is one of titanium alloy, stainless steel, aluminum alloy, or magnesium alloy, and the thickness of the directional control coating on the metal surface is 100-1000 nm.

[0028] Furthermore, in step three, the thermoplastic composite material to be joined is a polyetheretherketone (PEEK)-based thermoplastic composite material, specifically one of PEEK monomer, carbon fiber reinforced PEEK, or glass fiber reinforced PEEK; the thermal joining process is one of laser joining, friction stir joining, hot pressing joining, resistance welding, or induction joining.

[0029] The beneficial effects of this invention are:

[0030] The present invention discloses a method for preparing a chemically regulated block copolymer for use at the thermal interface of a metal and a thermoplastic composite material. This method can induce high-density chemical bonding and secondary interactions between the atoms and functional groups of the metal and the thermoplastic composite material to be bonded. The high-density Si-OM (metal atom) covalent bonds are formed by the de-alcoholization reaction of the KH570 polymer segment in the chemically regulated block copolymer for use at the thermal interface of a metal and a thermoplastic composite material under the action of a catalyst. The polar functional groups of the poly(glycidyl methacrylate) polymer segment interact with the oxygen-containing functional groups (carbonyl groups, ether bonds) inside the thermoplastic composite material in a high-density manner. This invention utilizes a chemically regulated block copolymer prepared for use at the thermal bonding interface of metal and thermoplastic composites. This method employs chemical-scale directional regulation of the interface, leveraging the high polymer interaction density and ease of directional chemical bonding based on atomic composition. This significantly enhances the interfacial bonding strength of metal and thermoplastic composites. By controlling the concentration of the chemically regulated block copolymer and the molecular weight ratio of functional segments within the block copolymer, the interfacial bonding strengthening effect can be adjusted. Furthermore, the regulation size can be adjusted according to the bonding region. The regulation process is simple, convenient, applicable to various thermal bonding processes, and highly adaptable.

[0031] This invention discloses a method for regulating chemically controlled block copolymers applied to the thermal bonding interface of metal and thermoplastic composites. Unlike existing technologies for regulating the thermal bonding interface of metal and thermoplastic composites, this invention creatively addresses the difficulties in inducing interfacial chemical interactions and the lack of clear mechanisms. It employs a chemically controlled block copolymer applied to the thermal bonding interface of metal and thermoplastic composites to achieve chemical bonding and secondary interactions on both sides of the metal and thermoplastic composite material, thus solving problems such as difficult interfacial bonding, uneven bonding regulation, and poor interfacial strengthening effects during the thermal bonding process of metal and thermoplastic composites. This method has promising application prospects in the field of thermal bonding of metal and thermoplastic composites. Attached Figure Description

[0032] Figure 1 This is a schematic diagram of the structure of a chemically regulated block copolymer applied to the thermal bonding interface of a metal and a thermoplastic composite material, as described in this invention.

[0033] Figure 2 The infrared spectrum of a chemically regulated block copolymer applied to the thermal bonding interface of a metal and thermoplastic composite material, as described in this invention;

[0034] Figure 3 Comparison of the tensile curves of the thermal joints obtained in Examples 3-5, Comparative Example 1, and Comparative Example 2;

[0035] Figure 4 The infrared spectrum of the thermal connection interface region between the TC4 titanium alloy sheet and the carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet in Example 3 is shown.

[0036] Figure 5 This diagram illustrates the interfacial mechanism of chemically scale-oriented regulation of the thermal bonding interface between TC4 titanium alloy sheet and carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet, using a chemically regulated block copolymer method applied to the thermal bonding interface of metal and thermoplastic composites. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described specific embodiments are merely a part of the embodiments of the invention, and not all of them. The components of the specific embodiments of the invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations, and the invention may also have other embodiments.

[0038] Therefore, the following detailed description of specific embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected specific embodiments of the invention. All other specific embodiments obtained by those skilled in the art based on these specific embodiments without inventive effort are within the scope of protection of this invention.

[0039] To further understand the invention's content, features, and effects, the following specific embodiments are provided, along with accompanying drawings. Figure 1 -Appendix Figure 5 Detailed explanation is as follows:

[0040] Example 1

[0041] A method for preparing a chemically regulated block copolymer for use at the thermal bonding interface of a metal and a thermoplastic composite material includes the following steps:

[0042] S1. Dissolve the initiator, copper bromide, ligand, reducing agent and glycidyl methacrylate in tetrahydrofuran to obtain the reaction system, which is then ready for use.

[0043] Furthermore, in step S1, the molar ratio of the initiator, copper bromide, ligand, reducing agent and glycidyl methacrylate is 1:0.4:0.4:0.4:n, and the molar volume ratio of glycidyl methacrylate to tetrahydrofuran is 1 mol: 1000 ml.

[0044] Furthermore, the initiator in step S1 is one of ethyl 2-bromopropionate, methyl 2-bromopropionate, or methyl 2-bromoisobutyrate; the ligand is one of pentamethyldiethylenetriamine, 2,2-bipyridine, or hexamethyltriethylenetetramine; and the reducing agent is one of stannous octoate or ascorbic acid.

[0045] S2. The reaction system obtained in step S1 is placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. The mixture is stirred for a certain time under certain temperature conditions to obtain poly(glycidyl methacrylate)-bromine.

[0046] Furthermore, the temperature condition in step S2 is 50℃, and the stirring time is 24h;

[0047] S3. The polyglycidyl methacrylate-bromine obtained in step S2 is extracted by chromatography column to obtain a clear solution and added dropwise to distilled water to obtain a white precipitate. After dehydration treatment, polyglycidyl methacrylate-bromine solid is obtained.

[0048] Furthermore, in step S3, the volume ratio of distilled water to tetrahydrofuran added is 30:1;

[0049] S4. The poly(glycidyl methacrylate)-bromine obtained in step S3 was added to copper bromide, ligand, reducing agent and KH570 silane coupling agent in tetrahydrofuran, and then placed in a spherical reaction flask for dehydration and deoxygenation using a double-row tube system. After stirring for a certain time under certain temperature conditions, the reaction product was extracted by chromatography column to clarify the solution and then distilled under reduced pressure to obtain a chemically regulated copolymer of the thermal connection interface of metal and thermoplastic composite material.

[0050] Furthermore, in step S4, the molar ratio of polyglycidyl methacrylate-bromine, copper bromide, ligand, reducing agent, and KH570 silane coupling agent is 1:0.4:0.4:0.4:m / n, and the molar volume ratio of KH570 silane coupling agent to tetrahydrofuran is 1 mol:10000 ml; the specific temperature conditions in step S4 are 50℃ and the stirring time is 24 h.

[0051] The chemical structural formula of the chemically regulated copolymer at the thermal bonding interface between the metal and the thermoplastic composite is as follows:

[0052]

[0053] In the chemical structural formula, n = 10 to 1000, m = n × (10 to 30%).

[0054] This embodiment provides a method for preparing a chemically regulated block copolymer for the thermal bonding interface of a metal and a thermoplastic composite material. This chemically regulated block copolymer can induce high-density chemical bonding and secondary interactions between the atoms and functional groups of the metal and thermoplastic composite material to be bonded. High-density Si-OM (metal atom) covalent bonds are formed through a de-alcoholization reaction of the KH570 polymer segment in the chemically regulated block copolymer under the action of a catalyst, with hydroxyl groups adsorbed on the metal surface reacting with the KH570 polymer segment in the chemically regulated block copolymer. The polar functional groups of the poly(glycidyl methacrylate) polymer segment undergo high-density secondary interactions with the oxygen-containing functional groups (carbonyl groups, ether bonds) inside the thermoplastic composite material, enabling directional chemical-scale regulation of both sides of the thermal bonding interface of the metal and thermoplastic composite material.

[0055] Example 2

[0056] This embodiment provides a specific preparation method for a chemically regulated block copolymer applied to the thermal bonding interface of a metal and thermoplastic composite material, as described in Example 1.

[0057] The synthesis steps of a chemically regulated block copolymer for use at the thermal bonding interface of metal and thermoplastic composites are as follows:

[0058] 0.113125 g of ethyl 2-bromopropionate, 0.5075 g of copper bromide, 0.0435 g of pentamethyldiethylenetriamine, 0.10125 g of stannous octoate, and 3.55 g of glycidyl methacrylate were dissolved in 25 ml of tetrahydrofuran. The reaction system was placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. After stirring at 50 °C for 24 hours, poly(glycidyl methacrylate)-bromo with a molecular weight of 5680 was obtained. The reaction system was extracted into a clear solution by chromatography and added dropwise to 750 ml of distilled water to obtain a white precipitate. After dehydration for 24 hours, solid poly(glycidyl methacrylate)-bromo with a molecular weight of 5680 was obtained.

[0059] The obtained poly(glycidyl methacrylate)-bromine solid with a molecular weight of 5680 was dissolved in 12.5 ml of tetrahydrofuran, and 0.5075 g of copper bromide, 0.0435 g of pentamethyldiethylenetriamine, 0.10125 g of stannous octoate and 0.62 g of KH570 silane coupling agent were added to it. The reaction system was placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. After stirring at 50 °C for 24 hours, the reaction product was extracted by chromatography and the clarified solution was distilled under reduced pressure at 40 °C to obtain a chemically regulated block copolymer with a molecular weight matching of poly(glycidyl methacrylate) (5680)-poly(γ-methacryloyloxypropyltrimethoxysilane) (10%), which can be used for thermal bonding interfaces of metal and thermoplastic composites.

[0060] Figure 2 This is the infrared spectrum of a chemically regulated block copolymer used in the thermal bonding interface of metal and thermoplastic composites; through... Figure 2 It can be seen that it is located at 908cm -1 The presence of epoxy groups indicates that the epoxy groups in glycidyl methacrylate have been successfully introduced into a chemically regulated block copolymer used in the thermal bonding interface of metal and thermoplastic composites, located at 1676 cm⁻¹. -1 The presence of Si-OC indicates that Si-OC in PKH570 has been successfully introduced into a chemically regulated block copolymer used for thermal bonding interfaces between metals and thermoplastic composites, located at 1638 cm⁻¹. -1 The disappearance of the typical C=C absorption peak indicates that a polymerization reaction has occurred. In summary, this chemically regulated block copolymer for use at the thermal bonding interface of metal and thermoplastic composite materials has been successfully prepared.

[0061] Example 3

[0062] This embodiment provides a method for chemically scale-oriented control of the thermal interface between TC4 titanium alloy sheet and carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet using a chemically regulated block copolymer prepared in Example 2 for application at the thermal interface of metal and thermoplastic composite materials.

[0063] The model and dimensions of the TC4 titanium alloy sheet to be connected to the carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet in this embodiment are as follows:

[0064] TC4 titanium alloy sheet is 50mm long, 30mm wide, and 1.5mm thick;

[0065] The carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet is 50mm long, 30mm wide, and 2mm thick.

[0066] Before assembly, the TC4 titanium alloy and carbon fiber reinforced polyetheretherketone (CF-PEEK) sheets were cleaned in a mixture of acetone and alcohol for 60 seconds to remove surface oil. The cleaned CF-PEEK sheets were then dried in an 80°C oven for 2 hours. The TC4 titanium alloy sheets were then acid-washed in a mixed acid solution of 80% deionized water, 15% hydrochloric acid, and 5% hydrofluoric acid for 1 minute, followed by drying.

[0067] The specific control method in this embodiment is as follows:

[0068] A chemically regulated block copolymer for thermal bonding interfaces of metal and thermoplastic composites, prepared in Example 2 with a molecular weight matched as poly(5680)-poly(γ-methacryloyloxypropyltrimethoxysilane) (10%), was dissolved in tetrahydrofuran, resulting in a solution with a concentration of 0.01 mol / mL. 0.005 g / mL of dibutyltin dilaurate was added to the solution, and the mixture was thoroughly stirred. The solution was sprayed onto the surface of a TC4 titanium alloy sheet, dried at 80°C to obtain a 500 nm thick directional regulated coating, and left in air for 24 hours to obtain the directional regulated coating. This completes the preparation of a directional regulated coating of a chemically regulated block copolymer for thermal bonding interfaces of metal and thermoplastic composites on the surface of the TC4 sheet to be bonded.

[0069] The TC4 titanium alloy with a directional control coating cured on its surface is tightly overlapped with a carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet with an overlap width of 20mm. A thermal connection joint between the TC4 titanium alloy and the carbon fiber reinforced polyether ether ketone (CF-PEEK) is obtained by laser joining process after the interface directional control is obtained.

[0070] The specific laser connection process parameters in this embodiment are as follows:

[0071] Laser power: 850W, defocusing amount: +6mm, laser scanning speed: 0.8m / min, welding length: 30mm, interface clamping pressure: 0.3MPa, laser scanning surface: TC4 titanium alloy surface.

[0072] Example 4

[0073] This embodiment provides a method for chemically scale-oriented control of the thermal interface between TC4 titanium alloy sheet and carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet using a chemically regulated block copolymer applied to the thermal interface of metal and thermoplastic composite materials, as proposed in Example 1.

[0074] In this embodiment, a specific preparation method for a chemically regulated block copolymer applied to the thermal bonding interface of a metal and a thermoplastic composite material is as follows:

[0075] 0.113125 g of ethyl 2-bromopropionate, 0.5075 g of copper bromide, 0.0435 g of pentamethyldiethylenetriamine, 0.10125 g of stannous octoate, and 3.55 g of glycidyl methacrylate were dissolved in 25 ml of tetrahydrofuran. The reaction system was placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. After stirring at 50 °C for 24 hours, poly(glycidyl methacrylate)-bromo with a molecular weight of 5680 was obtained. The reaction system was extracted into a clear solution by chromatography and added dropwise to 750 ml of distilled water to obtain a white precipitate. After dehydration for 24 hours, solid poly(glycidyl methacrylate)-bromo with a molecular weight of 5680 was obtained.

[0076] The obtained poly(glycidyl methacrylate)-bromine solid with a molecular weight of 5680 was dissolved in 25 ml of tetrahydrofuran as a ligand, and 0.5075 g of copper bromide, 0.0435 g of pentamethyldiethylenetriamine, 0.10125 g of stannous octoate and 1.24 g of KH570 silane coupling agent were added to the mixture. The reaction system was placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. After stirring at 50 °C for 24 hours, the reaction product was extracted by chromatography to obtain a clear solution, which was then distilled under reduced pressure at 40 °C to obtain a chemically regulated block copolymer with a molecular weight matching of poly(glycidyl methacrylate) (5680)-poly(γ-methacryloyloxypropyltrimethoxysilane) (20%), which can be used for thermal bonding interfaces of metal and thermoplastic composites.

[0077] The model and dimensions of the TC4 titanium alloy sheet to be connected to the carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet in this embodiment are as follows:

[0078] TC4 titanium alloy sheet is 50mm long, 30mm wide, and 1.5mm thick;

[0079] The carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet is 50mm long, 30mm wide, and 2mm thick.

[0080] Before assembly, the TC4 titanium alloy and carbon fiber reinforced polyetheretherketone (CF-PEEK) sheets were cleaned in a mixture of acetone and alcohol for 60 seconds to remove surface oil. The cleaned CF-PEEK sheets were then dried in an 80°C oven for 2 hours. The TC4 titanium alloy sheets were then acid-washed in a mixed acid solution of 80% deionized water, 15% hydrochloric acid, and 5% hydrofluoric acid for 1 minute, followed by drying.

[0081] The specific control method in this embodiment is as follows:

[0082] A chemically regulated block copolymer for thermal bonding interfaces of metal and thermoplastic composites, prepared in this embodiment with a molecular weight matched as poly(5680)-poly(γ-methacryloyloxypropyltrimethoxysilane) (20%), was dissolved in tetrahydrofuran, resulting in a solution with a concentration of 0.01 mol / mL. 0.005 g / mL of dibutyltin dilaurate was added to the solution, and the mixture was thoroughly stirred. The solution was sprayed onto the surface of a TC4 titanium alloy sheet, dried at 80°C to obtain a 500 nm thick directional regulated coating, and left in air for 24 hours to obtain the directional regulated coating. This completes the preparation of a directional regulated coating of a chemically regulated block copolymer for thermal bonding interfaces of metal and thermoplastic composites on the surface of the TC4 sheet to be bonded.

[0083] The TC4 titanium alloy with a directional control coating cured on its surface is tightly overlapped with a carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet with an overlap width of 20mm. A thermal connection joint between the TC4 titanium alloy and the carbon fiber reinforced polyether ether ketone (CF-PEEK) is obtained by laser joining process after the interface directional control is obtained.

[0084] The specific laser connection process parameters in this embodiment are as follows:

[0085] Laser power: 850W, defocusing amount: +6mm, laser scanning speed: 0.8m / min, welding length: 30mm, interface clamping pressure: 0.3MPa, laser scanning surface: TC4 titanium alloy surface.

[0086] Example 5

[0087] This embodiment provides a method for chemically scale-oriented control of the thermal interface between TC4 titanium alloy sheet and carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet using a chemically regulated block copolymer applied to the thermal interface of metal and thermoplastic composite materials, as proposed in Example 1.

[0088] In this embodiment, a specific preparation method for a chemically regulated block copolymer applied to the thermal bonding interface of a metal and a thermoplastic composite material is as follows:

[0089] 0.113125 g of ethyl 2-bromopropionate, 0.5075 g of copper bromide, 0.0435 g of pentamethyldiethylenetriamine, 0.10125 g of stannous octoate, and 3.55 g of glycidyl methacrylate were dissolved in 25 ml of tetrahydrofuran. The reaction system was placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. After stirring at 50 °C for 24 hours, poly(glycidyl methacrylate)-bromo with a molecular weight of 5680 was obtained. The reaction system was extracted into a clear solution by chromatography and added dropwise to 750 ml of distilled water to obtain a white precipitate. After dehydration for 24 hours, solid poly(glycidyl methacrylate)-bromo with a molecular weight of 5680 was obtained.

[0090] The obtained poly(glycidyl methacrylate)-bromine solid with a molecular weight of 5680 was dissolved in 37.5 ml of tetrahydrofuran, and 0.5075 g of copper bromide, 0.0435 g of pentamethyldiethylenetriamine, 0.10125 g of stannous octoate and 1.86 g of KH570 silane coupling agent were added to it. The reaction system was placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. After stirring at 50 °C for 24 hours, the reaction product was extracted by chromatography and the clarified solution was distilled under reduced pressure at 40 °C to obtain a chemically regulated block copolymer with a molecular weight matching of poly(glycidyl methacrylate) (5680)-poly(γ-methacryloyloxypropyltrimethoxysilane) (30%), which can be used for thermal bonding interfaces of metal and thermoplastic composites.

[0091] The model and dimensions of the TC4 titanium alloy sheet to be connected to the carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet in this embodiment are as follows:

[0092] TC4 titanium alloy sheet is 50mm long, 30mm wide, and 1.5mm thick;

[0093] The carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet is 50mm long, 30mm wide, and 2mm thick.

[0094] Before assembly, the TC4 titanium alloy and carbon fiber reinforced polyetheretherketone (CF-PEEK) sheets were cleaned in a mixture of acetone and alcohol for 60 seconds to remove surface oil. The cleaned CF-PEEK sheets were then dried in an 80°C oven for 2 hours. The TC4 titanium alloy sheets were then acid-washed in a mixed acid solution of 80% deionized water, 15% hydrochloric acid, and 5% hydrofluoric acid for 1 minute, followed by drying.

[0095] The specific control method in this embodiment is as follows:

[0096] A chemically regulated block copolymer for thermal bonding interfaces of metal and thermoplastic composites, prepared in this embodiment with a molecular weight matched as poly(5680)-poly(γ-methacryloyloxypropyltrimethoxysilane) (30%), was dissolved in tetrahydrofuran, resulting in a solution with a concentration of 0.01 mol / mL. 0.005 g / mL of dibutyltin dilaurate was added to the solution, and the mixture was thoroughly stirred. The solution was sprayed onto the surface of a TC4 titanium alloy sheet, dried at 80°C to obtain a 500 nm thick directional regulated coating, and left in air for 24 hours to obtain the directional regulated coating. This completes the preparation of a directional regulated coating of a chemically regulated block copolymer for thermal bonding interfaces of metal and thermoplastic composites on the surface of the TC4 sheet to be bonded.

[0097] The TC4 titanium alloy with a directional control coating cured on its surface is tightly overlapped with a carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet with an overlap width of 20mm. A thermal connection joint between the TC4 titanium alloy and the carbon fiber reinforced polyether ether ketone (CF-PEEK) is obtained by laser joining process after the interface directional control is obtained.

[0098] The specific laser connection process parameters in this embodiment are as follows:

[0099] Laser power: 850W, defocusing amount: +6mm, laser scanning speed: 0.8m / min, welding length: 30mm, interface clamping pressure: 0.3MPa, laser scanning surface: TC4 titanium alloy surface.

[0100] Comparative Example 1

[0101] This comparative example directly uses laser bonding to connect TC4 titanium alloy to carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet.

[0102] The models and dimensions of the TC4 titanium alloy sheet and the carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet to be connected in this comparative example are as follows:

[0103] TC4 titanium alloy sheet is 50mm long, 30mm wide, and 1.5mm thick;

[0104] The carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet is 50mm long, 30mm wide, and 2mm thick.

[0105] Before assembly, the TC4 titanium alloy and carbon fiber reinforced polyetheretherketone (CF-PEEK) sheets were cleaned in a mixture of acetone and alcohol for 60 seconds to remove surface oil. The cleaned CF-PEEK sheets were then dried in an 80°C oven for 2 hours. The TC4 titanium alloy sheets were then acid-washed in a mixed acid solution of 80% deionized water, 15% hydrochloric acid, and 5% hydrofluoric acid for 1 minute, followed by drying.

[0106] The TC4 titanium alloy and carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet are tightly overlapped with a 20mm overlap width; a thermal connection joint between the TC4 titanium alloy and the carbon fiber reinforced polyether ether ketone (CF-PEEK) is obtained through laser joining process.

[0107] The specific laser bonding process parameters for this comparative example are as follows:

[0108] Laser power: 850W, defocusing amount: +6mm, laser scanning speed: 0.8m / min, welding length: 30mm, interface clamping pressure: 0.3MPa, laser scanning surface: TC4 titanium alloy surface.

[0109] Comparative Example 2

[0110] In this comparative example, glycidyl methacrylate and KH570 silane coupling agent were mixed and dissolved in ethyl acetate in the same proportion as in Example 2 to prepare a chemically regulated block copolymer for the thermal interface of metal and thermoplastic composite materials. After azobisisobutyronitrile was added and the mixture was fully reacted, a random copolymer of glycidyl methacrylate and γ-methacryloyloxypropyltrimethoxysilane was obtained. This copolymer was then used to regulate the thermal interface of TC4 titanium alloy sheet and carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet.

[0111] The models and dimensions of the TC4 titanium alloy sheet and the carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet to be connected in this comparative example are as follows:

[0112] TC4 titanium alloy sheet is 50mm long, 30mm wide, and 1.5mm thick;

[0113] The carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet is 50mm long, 30mm wide, and 2mm thick.

[0114] Before assembly, the TC4 titanium alloy and carbon fiber reinforced polyetheretherketone (CF-PEEK) sheets were cleaned in a mixture of acetone and alcohol for 60 seconds to remove surface oil. The cleaned CF-PEEK sheets were then dried in an 80°C oven for 2 hours. The TC4 titanium alloy sheets were then acid-washed in a mixed acid solution of 80% deionized water, 15% hydrochloric acid, and 5% hydrofluoric acid for 1 minute, followed by drying.

[0115] The specific adjustment method for this comparative ratio is as follows:

[0116] 0.005 g / ml of dibutyltin dilaurate was added to the random copolymer solution of glycidyl methacrylate and γ-methacryloxypropyltrimethoxysilane prepared in this comparative example, and the mixture was thoroughly stirred. The solution was sprayed onto the surface of a TC4 titanium alloy plate, and after drying at 80°C, a directional control coating with a thickness of 500 nm was obtained. After being placed in air for 24 hours, the directional control coating was obtained, completing the preparation of the functional block copolymer directional control coating on the surface of the TC4 plate to be bonded.

[0117] A TC4 titanium alloy with a functional block copolymer directional control coating cured on its surface is tightly overlapped with a carbon fiber reinforced polyether ether ketone (CF-PEEK) sheet with an overlap width of 20 mm. A thermal connection joint between the TC4 titanium alloy and the carbon fiber reinforced polyether ether ketone (CF-PEEK) is obtained through a laser bonding process after the interface directional control is achieved.

[0118] The specific laser connection process parameters in this embodiment are as follows:

[0119] Laser power: 850W, defocusing amount: +6mm, laser scanning speed: 0.8m / min, welding length: 30mm, interface clamping pressure: 0.3MPa, laser scanning surface: TC4 titanium alloy surface.

[0120] Figure 3 The table shows a comparison of the tensile curves of the thermally bonded joints obtained in Examples 3-5, Comparative Example 1, and Comparative Example 2. The specific tensile strengths are shown in Table 1. Figure 3It can be seen that compared to the untreated TC4 / CF-PPEK joint shear strength of 34 N / mm, the shear strength of the TC4 / CF-PPEK joint regulated by the introduction of a random copolymer with functionally controlled groups is 75 N / mm, an increase of 120.5%. This indicates that it is feasible to improve the bonding strength by introducing functional groups to directionally induce chemical bonding and intermolecular interactions at the interface between metal and thermoplastic composites. After transforming the random copolymer with functionally controlled groups into a chemically controlled block copolymer for use at the thermal interface of metal and thermoplastic composites, the shear strength of the TC4 / CF-PPEK joint increased to 134.9 N / mm, an increase of 79.8% compared to the random copolymer state. This shows that the introduction of block copolymers promotes the ordering among those with the same functional groups, enhances the intermolecular force between functional groups, and thus improves the bonding strength and secondary interaction strength at the interface. This proves that the chemical regulation method for the thermal interface of metal and thermoplastic composites proposed in this invention is feasible for improving the bonding strength of the thermal interface of metal and thermoplastic composites. With the increase in atomic weight distribution within the block copolymer, the shear strength of the TC4 / CF-PPEK joints in Examples 4 and 5 further increased to 144.8 N / mm and 156.8 N / mm, respectively. This indicates that with the increase in molecular weight distribution, the interfacial bonding density increases, the probability of bonding per unit area increases, and the interfacial bonding strength increases accordingly.

[0121] Figure 4 The image shows the infrared spectrum of the thermal interface region between the TC4 titanium alloy sheet and the carbon fiber reinforced polyetheretherketone (CF-PEEK) sheet in Example 3. (Comparison) Figure 4 and Figure 2 It can be seen that, Figure 2 A chemically regulated block copolymer located at 1676 cm⁻¹ is applied to the thermal bonding interface of metal and thermoplastic composites. -1 The Si-OC bond disappears at the connection interface, while the TC4 side of the connection interface is located at 940cm. -1 The presence of Si-O-Ti bonds at this location indicates that the Si-OC bonds react with the hydroxyl groups adsorbed on the TC4 surface to form covalent bonds in a directional manner; simultaneously, at 908 cm⁻¹... -1 The epoxy groups are flooded to 901 cm at the CF-PPEK side interface. -1 CP-PEEK internal C=O(1643cm) -1 ), -O-(1217cm) -1 The blue shift occurred at 1657cm. -1 And redshifted to 1211cm -1This describes a chemically regulated interface for thermal bonding of metal and thermoplastic composites, where epoxy groups in the block copolymer interact with carbonyl groups and ether bonds in the CP-PEEK side polyether ether ketone matrix, resulting in high-density secondary interactions. The above analysis indicates that the chemically regulated interface for thermal bonding of metal and thermoplastic composites of this invention can achieve bilaterally directional induction of high-density chemical bonding and secondary interactions on the CFRTP side of TC4 during laser bonding, thereby enhancing joint performance.

[0122] Table 1 Comparison of tensile strength

[0123] Comparative Example 1 34 Comparative Example 2 75 Example 3 134.9 Example 4 144.8 Example 5 156.8

[0124] This invention provides a method for chemically regulating the thermal interface of metal-thermoplastic composites. This is achieved by introducing a chemically regulated block copolymer at the interface, which forms high-density covalent bonds with metal atoms and induces high-density van der Waals forces between the copolymer and the polar functional groups within the thermoplastic composite. Furthermore, the reinforcing effect can be adjusted by controlling the molecular weight percentage of the block copolymer in the coating.

[0125] Compared to Comparative Example 1, Comparative Example 2 showed a 120.5% increase in joint strength, demonstrating the feasibility of introducing functional groups to improve interfacial bonding strength by directionally inducing chemical bonding and intermolecular interactions at the interface between metal and thermoplastic composites. Compared to Comparative Example 2, Example 3 showed a 79.8% increase in joint strength, indicating that the introduction of block copolymers promoted order among functional groups with the same functional groups, increased the intermolecular force between functional groups, and thus improved the interfacial bonding strength. Compared to Example 3, Examples 4 and 5 showed a further increase in the shear strength of the TC4 / CF-PPEK joint, demonstrating the feasibility of increasing the bonding density and bonding probability per unit area by increasing the molecular weight percentage. This further demonstrates the feasibility of the chemical regulation method for the thermal bonding interface of metal and thermoplastic composites proposed in this invention to improve the interfacial bonding strength of metal and thermoplastic composites.

[0126] Example 6

[0127] A method for regulating chemically controlled block copolymers applied to the thermal bonding interface of metal and thermoplastic composites, based on the chemically controlled block copolymers applied to the thermal bonding interface of metal and thermoplastic composites described in Example 1, includes the following steps:

[0128] Step 1: Dissolve the chemically regulated block copolymer and catalyst used in the thermal bonding interface of metal and thermoplastic composite materials in an organic solvent to obtain a chemically regulated block copolymer solution used in the thermal bonding interface of metal and thermoplastic composite materials.

[0129] Furthermore, the catalyst mentioned in step one is one of dibutyltin dilaurate and stannous octoate, and the organic solvent is one of dichloromethane, tetrahydrofuran, toluene, or chloroform; the concentration of the catalyst in the chemically regulated block copolymer solution applied to the thermal interface of metal and thermoplastic composite materials is 0.001–0.01 g / mL, and the concentration of the chemically regulated block copolymer applied to the thermal interface of metal and thermoplastic composite materials is 0.001–0.01 mol / mL;

[0130] Step 2: Spray the chemically regulated block copolymer solution obtained in Step 1 onto the surface of the metal to be bonded, and dry it at room temperature for 24 hours to obtain a metal with a directional regulated coating cured on the surface.

[0131] Furthermore, in step two, the metal to be connected is one of titanium alloy, stainless steel, aluminum alloy or magnesium alloy, and the thickness of the directional control coating on the metal surface is 100 to 1000 nm.

[0132] Step 3: Assemble the metal with the directional control coating on its surface obtained in Step 2 and the thermoplastic composite material to be joined in an overlapping manner, and obtain a thermal connection joint between the metal and the thermoplastic composite material after the interface directional control through a thermal connection process, so as to realize the directional induction of high-density covalent bonds and secondary interactions at the thermal connection interface between the metal and the thermoplastic composite material.

[0133] Furthermore, in step three, the thermoplastic composite material to be joined is a polyetheretherketone (PEEK)-based thermoplastic composite material, specifically one of PEEK monomer, carbon fiber reinforced PEEK, or glass fiber reinforced PEEK; the thermal joining process is one of laser joining, friction stir joining, hot pressing joining, resistance welding, or induction joining.

[0134] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0135] Although this application has been described above with reference to specific embodiments, various modifications can be made and components can be replaced with equivalents without departing from the scope of this application. In particular, as long as there is no structural conflict, the features in the specific embodiments disclosed in this application can be combined with each other in any way. The lack of an exhaustive description of these combinations in this specification is merely for the sake of brevity and resource conservation. Therefore, this application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing chemically regulated block copolymers for use at the thermal bonding interface of metals and thermoplastic composites, characterized in that, Includes the following steps: S1. Dissolve the initiator, copper bromide, ligand, reducing agent and glycidyl methacrylate in tetrahydrofuran to obtain the reaction system, which is then ready for use; S2. The reaction system obtained in step S1 is placed in a spherical reaction flask and dehydrated and deoxygenated using a double-row tube system. The mixture is stirred for a certain time under certain temperature conditions to obtain poly(glycidyl methacrylate)-bromine. S3. The polyglycidyl methacrylate-bromine obtained in step S2 is extracted by chromatography and the clear solution is added dropwise to distilled water to obtain a white precipitate. After dehydration, polyglycidyl methacrylate-bromine solid is obtained. S4. The poly(glycidyl methacrylate)-bromine obtained in step S3 is added to copper bromide, ligand, reducing agent and KH570 silane coupling agent in tetrahydrofuran, and then placed in a spherical reaction flask for dehydration and deoxygenation using a double-row tube system. After stirring for a certain time under certain temperature conditions, the reaction product is extracted by chromatography column to clarify the solution and then distilled under reduced pressure to obtain a chemically regulated copolymer of the thermal bonding interface of metal and thermoplastic composite material. The chemical structural formula of the chemically regulated copolymer at the thermal bonding interface between the metal and the thermoplastic composite is as follows: In the chemical structural formula, n = 10~1000, m = n × (10~30%).

2. The method for preparing a chemically regulated block copolymer for the thermal bonding interface of a metal and a thermoplastic composite material according to claim 1, characterized in that, In step S1, the molar ratio of initiator, copper bromide, ligand, reducing agent and glycidyl methacrylate is 1:0.4:0.4:0.4:n, and the molar volume ratio of glycidyl methacrylate to tetrahydrofuran is 1 mol: 1000 ml.

3. A method for preparing a chemically regulated block copolymer for the thermal bonding interface of a metal and a thermoplastic composite material according to claim 1 or 2, characterized in that, The initiator in step S1 is ethyl 2-bromopropionate, the ligand is one of pentamethyldiethylenetriamine, 2,2-bipyridine or hexamethyltriethylenetetramine, and the reducing agent is one of stannous octoate or ascorbic acid.

4. The method for preparing a chemically regulated block copolymer for the thermal bonding interface of a metal and a thermoplastic composite material according to claim 3, characterized in that, The specific temperature conditions in step S2 are 50-60℃ and the stirring time is 24-30h.

5. The method for preparing a chemically regulated block copolymer for the thermal bonding interface of a metal and a thermoplastic composite material according to claim 4, characterized in that, In step S3, the volume ratio of distilled water to tetrahydrofuran added is 30:

1.

6. The method for preparing a chemically regulated block copolymer for the thermal bonding interface of a metal and a thermoplastic composite material according to claim 5, characterized in that, In step S4, the molar ratio of polyglycidyl methacrylate-bromine, copper bromide, ligand, reducing agent and KH570 silane coupling agent is 1:0.4:0.4:0.4:m, and the molar volume ratio of KH570 silane coupling agent to tetrahydrofuran is 1 mol: 10000 ml; the specific temperature conditions in step S4 are 50-60℃, and the stirring time is 24-30 h.

7. A method for regulating a chemically regulated block copolymer applied to the thermal bonding interface of a metal and a thermoplastic composite material, based on the chemically regulated block copolymer applied to the thermal bonding interface of a metal and a thermoplastic composite material as described in any one of claims 1-6, characterized in that, Includes the following steps: Step 1: Dissolve the chemically regulated block copolymer and catalyst used in the thermal bonding interface of metal and thermoplastic composite materials in an organic solvent to obtain a chemically regulated block copolymer solution used in the thermal bonding interface of metal and thermoplastic composite materials. Step 2: Spray the chemically regulated block copolymer solution obtained in Step 1 onto the surface of the metal to be bonded, and dry it at room temperature for 24 hours to obtain a metal with a directional regulated coating cured on the surface. Step 3: Assemble the metal with the directional control coating obtained in Step 2 and the thermoplastic composite material to be joined in an overlapping manner, and obtain a thermal connection joint between the metal and the thermoplastic composite material after the interface directional control through a thermal connection process, so as to realize the directional induction of high-density covalent bonds and secondary interactions at the thermal connection interface between the metal and the thermoplastic composite material.

8. The method for regulating chemically controlled block copolymers applied to the thermal bonding interface of metal and thermoplastic composite materials according to claim 7, characterized in that, The catalyst mentioned in step one is one of dibutyltin dilaurate and stannous octoate, and the organic solvent is one of dichloromethane, tetrahydrofuran, toluene, or chloroform; the concentration of the catalyst in the chemically regulated block copolymer solution applied to the thermal interface of metal and thermoplastic composite is 0.001~0.01 g / ml, and the concentration of the chemically regulated block copolymer applied to the thermal interface of metal and thermoplastic composite is 0.001~0.01 mol / mL.

9. The method for regulating chemically controlled block copolymers applied to the thermal bonding interface of metal and thermoplastic composite materials according to claim 8, characterized in that, In step two, the metal to be connected is one of titanium alloy, stainless steel, aluminum alloy or magnesium alloy, and the thickness of the directional control coating on the surface of the metal is 100~1000nm.

10. The method for regulating chemically regulated block copolymers applied to the thermal bonding interface of metal and thermoplastic composite materials according to claim 9, characterized in that, In step three, the thermoplastic composite material to be joined is a polyetheretherketone (PEEK)-based thermoplastic composite material, specifically one of carbon fiber reinforced PEEK or glass fiber reinforced PEEK; the thermal joining process is one of laser joining, friction stir joining, hot pressing joining, resistance welding, or induction joining.

Citation Information

Patent Citations

  • Method for connecting plastic and metal heterostructure

    CN106393705A

  • Device and method for improving laser connection strength of metal part and plastic part

    CN114407372A

  • Bilateral high-density chemical bonding directional induction method for thermal connection interface of metal and thermoplastic composite material

    CN118744529A